Design, synthesis, anti-inflammatory activity evaluation, and structure-activities relationship (SAR) study of diarylpentanoid derivatives - Leong, Sze Wei (2014)
Diarylpentanoid is an incredible family of curcuminoid derivatives which had gained increasingly attention recently for its excellent biological importance such as antioxidant,anti-inflammatory and anti-cancer activities. 2,6-Bis-(4-hydroxy-3- methoxybenzylidene)cyclohexanone, a diarylpentanoid analog synthesized by our group previously which derived from curcumin with the lack of ethylene unit from the heptane bridge has displayed outstanding anti-inflammatory properties through its inhibition on monocyte chemoattractant protein-1 (MCP-1), interleukin 6 (IL-6), interleukin 10 (IL-10) and tumor necrosis factor alpha (TNF-α) indicates that structural modification on diarylpentanoid could be a promising strategy in discovery of highly potent antiinflammatory agents. In this study, one hundred and twenty-five diarylpentenediones and fourteen heterocyclic compounds were synthesized and evaluated for their anti-inflammatory and anti-oxidant activities through cell based nitric oxide assay and 2,2-diphenyl-1- picrylhydrazyl (DPPH) free radical scavenging analysis, respectively. The antiinflammatory evaluation showed that seventy-three compounds were successfully inhibit nitric oxide (NO) production on IFN-γ/LPS-stimulated RAW264.7 macrophages with the IC50 range of 4.18 to 79.87 μM. Among the active candidates, twelve compounds (9, 25, 28, 63, 64, 81, 83, 84, 86, 88, 106 and 115) displayed similar or greater NO inhibitory activity compared to curcumin (14.69 ± 0.240 μM) of which compounds 88 and 106 demonstrated the most significant NO suppression activity with IC50 values of 4.89 ± 0.312 and 4.18 ± 0.221 μM , respectively. The structure–activity relationship (SAR) study revealed that the presence of hydroxyl group in both rings is critical for bioactivity of these molecules. Besides, with the exception of polyphenolic derivatives,low electron density in ring-A and high electron density in ring-B are important for NO inhibition enhancements. Furthermore, pharmacophore mapping showed that hydroxyl groups substituent at both meta- and para- position of ring-B could be the finger print for highly active diarylpentanoid derivatives. On the other hand, the anti-oxidant evaluation showed that nine compounds (83, 87, 88,89, 90, 91, 92, 96, and 106) were significantly inhibit DPPH free radical scavenging with 2- to 4-fold better than curcumin (23.56 ± 1.112 μM) of which compound 92 demonstrate the most potent antioxidant activity with the IC50 value of 5.58 ± 0.257 μM.Simple SAR study revealed that the remarkable anti-oxidant properties of diarylpentenediones is only depends on the presence of 2’,5’- or 3’,4’-dihydroxy phenyl rings which indicates the structure skeleton doesn’t affect the activity. Therefore, it is conceivably concluded that the diarylpentenediones and their respective heterocyclic derivatives are potent families as anti-inflammatory agents.